Transatlantic Anglophone Literatures, 1776-1920 An Anthology - Hughes, Linda K.; Robbins, Sarah R.; Taylor, Andrew (Edinburgh University Press, 2023)
This anthology provides a single, convenient volume of diverse primary texts supporting the teaching and research field of Anglophone Transatlantic literature and print culture in the long nineteenth century. Focusing on ongoing and shared concerns and social practices across the long nineteenth century, the book's thematically-organised sections mark major Transatlantic social movements of that era as expressed, negotiated, and recorded through literary production. The book offers a range of tools and texts for innovative thinking, teaching, and exploration. Headnotes provide guidance on how individual selections arose from social and historical contexts and, often, suggest potential pairings with other selections. Annotations create student-friendly identification of key terms or allusions.